Expression profile analysis of microRNAs during hair follicle development in the sheep foetus. Issue 6 (3rd June 2019) - Yang, Han-Yu-Lu; Yang, Hua; Shi, Guo-Qing; Shen, Min; Yang, Jing–Quan; Yang, Yong-Lin; Liu, Xiao-Jun
ABSTRACT: MicroRNAs (miRNAs) regulate the development and growth cycle of hair follicles (HFs). The molecular mechanism by which miRNAs determine the development of HFs in the sheep foetus remains elusive. In this study, the expression profiles of miRNAs at 11 development periods (45, 55, 65, 75, 85, 95, 105, 115, 125, 135 and 145 d) in sheep foetus skin were analysed by high-throughput sequencing and bioinformatics analysis. A total of 72 conserved miRNAs, 44 novel miRNAs and 32 known miRNAs were significantly differentially expressed. qRT-PCR results for 18 miRNAs were consistent with the sequencing data. 85 d of foetal development was the starting point for secondary hair follicle (SF) development according to tissue morphology and cluster analysis. In SF development, the prolactin signalling pathway and platelet activation played important roles, and 10 miRNAs were potential candidate miRNAs in SF initiation. Graphical abstract: : During 85d fetal development, 19 miRNAs were significantly up-regulated and 18 miRNAs were significantly down-regulated in initiation of secondary hair follicle growth